Le rôle des créanciers et des institutions financières dans la survie des entreprises en difficulté en droit belge - Foriers, Paul-Alain (Les Cahiers de droit, 1981)
In the first part of this article, Me Foriers explains the Belgium Laws on collective procedures and the peculiar and interesting efforts of the Bankruptcy Courts to detect the legal signals of a failing enterprise while it is still possible to avoid bankruptcy as well as the means used to redress the situation. In the second part, the author discusses the professional liability of the banking institution when a line of credit is granted or refused to an ailing enterprise. On this last aspect, Belgium Law is similar to French Law discussed in Professor's Gavalda article.